2021
DOI: 10.1038/s41398-021-01301-1
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter networks associated with attention and working memory deficit in ADHD across adolescence and adulthood

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a childhood-onset neuropsychiatric disorder and may persist into adulthood. Working memory and attention deficits have been reported to persist from childhood to adulthood. How neuronal underpinnings of deficits differ across adolescence and adulthood is not clear. In this study, we investigated gray matter of two cohorts, 486 adults and 508 adolescents, each including participants from ADHD and healthy controls families. Two cohorts both presented significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…Moreover, a study found a significant correlation of cuneus with inattentive scores in ADHD patients (40). In accordance with our results, fMRI studies revealed that there was a significant difference in connectivity between adult female and male ADHD patients in the middle frontal gyrus and cuneus (41, 42). Another study reported thinning of vortex in the cuneus compared to the control group, however, no gender effect was investigated (43).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a study found a significant correlation of cuneus with inattentive scores in ADHD patients (40). In accordance with our results, fMRI studies revealed that there was a significant difference in connectivity between adult female and male ADHD patients in the middle frontal gyrus and cuneus (41, 42). Another study reported thinning of vortex in the cuneus compared to the control group, however, no gender effect was investigated (43).…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the number of adults with ADHD has increased over the past 20 years, and some of this increase is explained by the persistence of ADHD symptoms in adulthood (Núñez-Jaramillo et al, 2021 ). As developmental brain processes alleviate some of the consequences of ADHD with neural normalization, the symptoms of hyperactivity disappear wherever they are in adulthood, but the persistence of the symptoms of inattention from childhood to adulthood is emphasized (Duan et al, 2021 ). As well as changes in ADHD symptoms throughout life, the variable and complex interaction of genetic and environmental factors is believed to play a role in the continuity of the disorder (Caye, et al, 2016 ).…”
mentioning
confidence: 99%
“…In addition, the age difference between used subjects may also lead to such inconsistency. Duan et al investigated GM networks of two cohorts (adults and adolescents) and found that adolescent patients showed different GM volume changes than that of adult patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on abnormalities of ADHD-related neural networks rather than discrete neural substrates coincides with the development trend of the neuroimaging research. For adults and adolescents, GM network identified in adults compromising the bilateral cerebellar tonsil and culmen and GM network identified in adolescents compromising the left cerebellar region were significantly associated with inattention ( 11 ). Yet, few sMRI studies have investigated the brain network changes based on GM in children with ADHD, which may uncover the neural mechanism of ADHD and provide an objective basis for the diagnosis of ADHD.…”
Section: Introductionmentioning
confidence: 99%